2013
DOI: 10.1001/jamaneurol.2013.3849
|View full text |Cite
|
Sign up to set email alerts
|

SQSTM1Mutations in French Patients With Frontotemporal Dementia or Frontotemporal Dementia With Amyotrophic Lateral Sclerosis

Abstract: IMPORTANCE Mutations in the SQSTM1 gene, coding for p62, are a cause of Paget disease of bone and amyotrophic lateral sclerosis (ALS). Recently, SQSTM1 mutations were confirmed in ALS, and mutations were also identified in 3 patients with frontotemporal dementia (FTD), suggesting a role for SQSTM1 in FTD. OBJECTIVE To evaluate the exact contribution of SQSTM1 to FTD and FTD with ALS (FTD-ALS) in an independent cohort of patients. DESIGN A SQSTM1 mutation was first identified in a multiplex family with FTD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 29 publications
2
111
0
Order By: Relevance
“…From the 6 rare variant we found, 4 (Table 1) had been previously reported in patients with ALS (Abramzon et al., 2012, Rubino et al., 2012). Among them, the SQSTM1 p.P392L is also known to be the most frequent SQSTM1 mutation in PDB (Laurin et al., 2002) and has also been reported in cases with FTD (Le Ber et al., 2013) and normal tension glaucoma (Scheetz et al., 2016), whereas VCP p.I27V and p.R159C have also been found in patients with IBMPFD (Chan et al., 2012, Rohrer et al., 2011), and the VCP p.I27V has also been recently reported in one sIBM patient (Weihl et al., 2015). The SQSTM1 p.A117V was reported in one early-onset AD patient (Cuyvers et al., 2015).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…From the 6 rare variant we found, 4 (Table 1) had been previously reported in patients with ALS (Abramzon et al., 2012, Rubino et al., 2012). Among them, the SQSTM1 p.P392L is also known to be the most frequent SQSTM1 mutation in PDB (Laurin et al., 2002) and has also been reported in cases with FTD (Le Ber et al., 2013) and normal tension glaucoma (Scheetz et al., 2016), whereas VCP p.I27V and p.R159C have also been found in patients with IBMPFD (Chan et al., 2012, Rohrer et al., 2011), and the VCP p.I27V has also been recently reported in one sIBM patient (Weihl et al., 2015). The SQSTM1 p.A117V was reported in one early-onset AD patient (Cuyvers et al., 2015).…”
Section: Resultsmentioning
confidence: 53%
“…A recent study reported a splice donor variant in SQSTM1 in a family with an autosomal dominant distal myopathy and also in an unrelated patient with sporadic distal myopathy (Bucelli et al., 2015). In addition, mutations in SQSTM1 are well known to be associated with familial and/or sporadic Paget disease of bone, ALS, and frontotemporal dementia (FTD) (Fecto et al., 2011, Kwok et al., 2014, Laurin et al., 2002, Le Ber et al., 2013, Miller et al., 2015, Rubino et al., 2012). Mutations in valosin-containing protein ( VCP ) gene are known to cause an inherited form of IBM with Paget disease and frontotemporal dementia (IBMPFD) (Gidaro et al., 2008, Watts et al., 2004) and have also been reported in cases with ALS and FTD (Johnson et al., 2010, Koppers et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1b) bvFTD behavioral variant frontotemporal dementia, MND motor neuron disease, PSP progressive supranuclear palsy, PNFA progressive non-fluent aphasia, F familial, S sporadic, U family history undocumented a Indicates variants not previously associated with ALS, FTLD or PDB [7, 11, 17, 28, 29, 33]. For a complete description of SQSTM1 mutations, see Supplementary table 2…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitin- and p62-positive inclusions composed of c9RAN proteins are a neuropathological hallmark in c9FTD/ALS 1418 , and mutations in p62 (refs. 30,31) and ubiquilin-2 (ref. 32) also result in ALS and FTD, indicating that UPS disruption may be a critical factor in c9FTD/ALS disease pathology.…”
mentioning
confidence: 99%